Experiences of membership in munno mubulwadde (your friend indeed) - a novel community-based health insurance scheme in Luwero district in rural central Uganda - Christine Nabanoba; Henry Zakumumpa (BMC, 2024)
Abstract Background Community-Based Health Insurance (CBHI) schemes are recognized as an important health financing pathway to achieving universal health coverage (UHC). Although previous studies have documented CBHIs in low-income countries, the majority of these have been provider-based. Non-provider based schemes have received comparatively less empirical attention. We sought to describe a novel non-provider based CBHI munno mubulwadde (your friend indeed) comprising informal sector members in rural central Uganda to understand the structure of the scheme, the experiences of scheme members in terms of the perceived benefits and barriers to retention in the scheme. Methods We report qualitative findings from a larger mixed-methods study. We conducted in-depth interviews with insured members (n = 18) and scheme administrators (n = 12). Four focus groups were conducted with insured members (38 participants). Data were inductively analyzed by thematic approach. Results Munno mubulwadde is a union of ten CBHI schemes coordinated by one administrative structure. Members were predominantly low-income rural informal sector households who pay annual premiums ranging from $17 and $50 annually and received medical care at 13 scheme-contracted private health facilities in Luwero District in Central Uganda. Insured members reported that scheme membership protected them from catastrophic health expenditure during episodes of sickness among household members, and especially so among households with children under-five who were reported to fall sick frequently, the scheme enabled members to receive perceived better quality health care at private providers in the study district relative to the nearest public facilities. The identified barriers to retention in the scheme include inconvenient dates for premium payment that are misaligned with harvest periods for cash crops (e.g. maize corn) on which members depended for their agrarian livelihoods, long distances to insurance-contracted private providers, falling prices of cash crops which diminished real incomes and affordability of insurance premiums in successive years after initial enrolment. Conclusion Munno mubulwadde was perceived by as a valuable financial cushion during episodes of illness by rural informal sector households. Policy interventions for promoting price stability of cash crops in central Uganda could enhance retention of members in this non-provider CBHI which is worthy of further research as an additional funding pathway for realizing UHC in Uganda and other low-income settings.